2021
DOI: 10.1002/jsfa.11484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baking technique for rice wine production and the characteristics of baked rice wine

Abstract: BACKGROUND Driven by the requirement to reduce the emission of wastewater in the brewing process, it is necessary to improve and innovate the fermentation technology of Chinese rice wine. In this study, the baking technique used to brew rice wine was explored. RESULTS Rice wine was brewed based on baked glutinous rice undergoing different high‐temperature stages, designated as baked rice wine (BRW1, BRW2 and BRW3). X‐ray diffraction and Fourier transform infrared analysis revealed that baking treatment under 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, compared with cooking, the CRW made from puffed glutinous rice has lower content of amino acids and alcohols . Compared with traditional CRW, baked rice wine contains more alcohol, esters, protein, ascorbic acid, amino acids, and total phenols . Enzymatic extrusion-processed CRW contains more reducing sugars and amino acids .…”
Section: Brewing Of Crwmentioning
confidence: 99%
See 2 more Smart Citations
“…However, compared with cooking, the CRW made from puffed glutinous rice has lower content of amino acids and alcohols . Compared with traditional CRW, baked rice wine contains more alcohol, esters, protein, ascorbic acid, amino acids, and total phenols . Enzymatic extrusion-processed CRW contains more reducing sugars and amino acids .…”
Section: Brewing Of Crwmentioning
confidence: 99%
“…85 Compared with traditional CRW, baked rice wine contains more alcohol, esters, protein, ascorbic acid, amino acids, and total phenols. 86 Enzymatic extrusion-processed CRW contains more reducing sugars and amino acids. 87 Compression bulking techniques may reduce the nutrients in CRW, but baking and enzymatic decompression methods can increase the protein and amino acid content.…”
Section: Brewing Of Crwmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon a previous study that demonstrated enhanced alcohol yield, fermentation efficiency, and antioxidant capacity of rice wine when fermented with baked glutinous rice, 5 this study aims to explore the potential advantages of employing baked red kojic rice for fermenting red starter wine. The appropriate baking temperature for red kojic rice was initially determined based on key enzyme activities and structural characteristics of starch granules post‐baking.…”
Section: Introductionmentioning
confidence: 99%
“…The primary raw materials for huangjiu production are rice, wheat, and wheat bran. In the pretreatment stage, the rice starch of steamed rice is enzymatically hydrolyzed and saccharified; 8 huangjiu is subsequently endowed with plentiful polysaccharides, oligosaccharides, proteins, amino acids, and flavor substances in the low‐temperature and long‐term fermentation by a unique variety of species (including Aspergillus spp., Rhizopus spp., Fusarium , Mucor , Bacillus , Saccharopolyspora , lactic acid bacteria and yeasts) 9 . Huangjiu is frequently ingested as an auxiliary medicine, which has potential applications in human health, although this has not been confirmed by research.…”
Section: Introductionmentioning
confidence: 99%